Induction of Tier 2 HIV-Neutralizing IgA Antibodies in Rhesus Macaques Vaccinated with BG505.664 SOSIP - Justin C. Smith; Prabhu S. Arunachalam; Traci H. Legere; Lisa A. Cavacini; Eric Hunter; Bali Pulendran; Rama R. Amara; Pamela A. Kozlowski (Vaccines)
Background: A goal of mucosal human immunodeficiency virus type 1 (HIV-1) vaccines is to generate mucosal plasma cells producing polymeric IgA (pIgA)-neutralizing antibodies at sites of viral entry. However, vaccine immunogens capable of eliciting IgA neutralizing antibodies (nAbs) that recognize tier 2 viral isolates have not yet been identified. Methods: To determine if stabilized native-like HIV-1 envelope (Env) trimers could generate IgA nAbs, we purified total IgA and IgG from the banked sera of six rhesus macaques that had been found in a previous study to develop serum nAbs after subcutaneous immunization with BG505.664 SOSIP and 3M-052 adjuvant, which is a TLR7/8 agonist. The neutralization of autologous tier 2 BG505 T332N pseudovirus by the IgA and IgG preparations was measured using the TZM-bl assay. Anti-SOSIP binding antibodies (bAbs) were measured by ELISA. Results: The IgG samples were found to have significantly greater levels of both nAb and bAb. However, after normalizing the nAb titer relative to the concentration of bAb, SOSIP-specific IgA purified from 2/6 animals was found to neutralize just as effectively as SOSIP-specific IgG, and in 3/6 animals, neutralization by the specific IgA was significantly greater. The more potent neutralization by IgA in these three animals was associated with a higher percentage of anti-SOSIP J chain-bound (polymeric) antibody. Conclusions: The parenteral vaccination of nonhuman primates with BG505.664 SOSIP generates HIV-1 tier 2 IgA nAbs in serum, including SOSIP-specific polymeric IgA, which appears to neutralize more efficiently than monomeric IgA or IgG. Mucosal delivery of this SOSIP or other stable Env trimers could generate locally synthesized polymeric IgA nAbs in mucosal tissues and secretions.